A defined range of guard cell calcium oscillation parameters encodes stomatal movements - Allen, Gethyn J.; Chu, Sarah P.; Harrington, Carrie L.; Schumacher, Karin; Hoffmann, Thomas; Tang, Yat Y.; Grill, Erwin; Schroeder, Julian I. (Nature, 2001)
Oscillations in cytosolic calcium concentration ([Ca2+]cyt) are central regulators of signal transduction cascades1, although the roles of individual [Ca2+]cyt oscillation parameters in regulating downstream physiological responses remain largely unknown. In plants, guard cells integrate environmental and endogenous signals to regulate the aperture of stomatal pores2 and [Ca2+]cyt oscillations are a fundamental component of stomatal closure3,4. Here we systematically vary [Ca2+]cyt oscillation parameters in Arabidopsis guard cells using a ‘calcium clamp’3,5,6,7 and show that [Ca2+]cyt controls stomatal closure by two mechanisms. Short-term ‘calcium-reactive’ closure occurred rapidly when [Ca2+]cyt was elevated, whereas the degree of long-term steady-state closure was ‘calcium programmed’ by [Ca2+]cyt oscillations within a defined range of frequency, transient number, duration and amplitude. Furthermore, in guard cells of the gca2 mutant8, [Ca2+]cyt oscillations induced by abscisic acid and extracellular calcium had increased frequencies and reduced transient duration, and steady-state stomatal closure was abolished. Experimentally imposing [Ca2+]cyt oscillations with parameters that elicited closure in the wild type restored long-term closure in gca2 stomata. These data show that a defined window of guard cell [Ca2+]cyt oscillation parameters programs changes in steady-state stomatal aperture.